2012
DOI: 10.1590/s1806-66902012000100003
|View full text |Cite
|
Sign up to set email alerts
|

Desempenho de cultivares de alface americana em resposta a diferentes doses de torta de filtro

Abstract: Desempenho de cultivares de alface americana em resposta a diferentes doses de torta de filtro 1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0
16

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 8 publications
1
21
0
16
Order By: Relevance
“…Dificuldades surgem quando diversos fatores ambientais afetam o crescimento e o desenvolvimento da cultura da alface. Sendo assim, foram conduzidos diversos estudos, para avaliar o desempenho de cultivares nas diferentes regiões do Brasil (Yuri et al, 2005;Santos et al, 2009;Blat et al, 2011, Guimarães et al, 2011Santana et al, 2012;Azevedo et al, 2013), com resultados significativos.…”
Section: Introductionunclassified
“…Dificuldades surgem quando diversos fatores ambientais afetam o crescimento e o desenvolvimento da cultura da alface. Sendo assim, foram conduzidos diversos estudos, para avaliar o desempenho de cultivares nas diferentes regiões do Brasil (Yuri et al, 2005;Santos et al, 2009;Blat et al, 2011, Guimarães et al, 2011Santana et al, 2012;Azevedo et al, 2013), com resultados significativos.…”
Section: Introductionunclassified
“…Many research studies have demonstrated the rise in crop productivity when they are fertilized with organic wastes [75]. In research using the ilter cake to fertilize diferent letuce cultivars increased yields were obtained in all cultivars evaluated.…”
Section: Solid Waste Management In Rural Areasmentioning
confidence: 96%
“…The need to eliminate amounts of agro-industrial residues that are not recycled has encouraged studies on alternative materials (GRIGATTI et al, 2007) such as sugarcane bagasse and filter cake from sugarcane mills (CATUNDA et al, 2008;SANTANA et al, 2012) as well as carbonized rice husks (SAIDELLES et al, 2009;TERRA et al, 2011) to substrates for seedling production. The use of raw materials that are easily found near seedling nurseries is also preferred.…”
Section: Introductionmentioning
confidence: 99%